The Development of Handout Images and Map of Concept In Material Classification of Living Things for Student of Class VII Junior High School 23 Padang - Viola Mecita; Relsas Yogica; Ristiono Ristiono; Mades Fifendy (Universitas Negeri Padang, 2019)
Learning media is one of the determinants of success in the learning process in school. The use of learning media will greatly help the effectiveness of the learning process and add one of the teaching materials that can be used by students in learning. But the role of learning media will not be seen if its use is not in accordance with the learning objectives that have been formulated. Students find it difficult to connect the concepts contained in the material, then students find it difficult to understand the material concepts. The material on biology teaching materials used is like narration, language that is difficult to understand, and the appearance is less attractive. To overcome this problem, the teacher needs to develop teaching materials that are expected to be interesting and easy to understand by students in understanding the concepts contained in biology learning material. Teaching materials developed are Handouts. This research is Development Research conducted at FMIPA UNP and Padang Junior High School 23, using the Plomp development model (2013). The subject of this study consisted of 2 lecturers of Biology Department FMIPA UNP, 1 Biology teacher at SMP 23 Padang, and 29 students in grade VII of SMP 23 Padang. The data in this study are data obtained from the validity test questionnaire and practicality test. This data includes primary data, namely data obtained directly from the research subject.From the research, produced a nuanced handout of drawings and concept maps of living class classification material for class VII students of SMP which were categorized as valid with a value of 4.50, stated to be very practical with a value of 4.60 by the teacher and very practical with a value of 4.40 by participants student.